The color palette in the artistic heritage of Shevchenko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Vocabulary to describe colors is always in the center of attention of scientists. The article deals with the functioning of the texts used in the Shevchenko the name of colour and their derivatives. A very broad compatibility appropriate tokens in the literal and figurative meanings.
Keywords: the name of colour; color words; derivative words; derivatives; thematic group standing epithet